Analisis Pengaruh Gaya Kepemimpinan, Pelatihan, dan Lingkungan Kerja Fisik terhadap Motivasi serta Dampaknya terhadap Kinerja Pegawai Badan Siber dan Sandi Negara - Sugito Efendi; Lantika Nandarini (FOCUS, 2020)
This study aims to determine the influence of Leadership Style, Training, and Physical Work Environment on Motivation and its impact on The Performance of Employees of National Cyber and Crypto Agency. The analysis method used in this study is SEM (Structural Equation Model). The results of this study showed that Leadership Style, Training, and Physical Work Environment have a positive and significant effect on Employee Motivation. In addition, Leadership Style, Training, and Physical Work Environment through Motivation have a positive and significant effect on Employee Performance. Motivation also has a positive and significant effect on Employee Performance.